Clinical and Radiologic Outcome of a Less Invasive, Low-Cost Surgical Technique of Osteoplastic Decompressive Craniectomy - Adeleye, Amos O. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2016)
Background Decompressive craniectomy (DC) has many technical details with significant constraining logistic/economic considerations in low-resource practice areas. We present a less invasive, cost-saving, and evidence-based technique of DC evolving in our practice.Methods Earlier, we reported a technique of hinge decompressive craniectomy (hDC), in which the frontotemporoparietal skull flap is hinged on the temporal muscle. In this article we describe further refinements of this temporal muscle hDC : The scalp flap is raised in a galeal-skeletonizing plane preserving the subgaleal fascia on the pericranium, ready for use for duraplasty after durotomy. We performed a descriptive analysis of the clinical outcome of this surgical technique in a prospective consecutive cohort of patients with traumatic brain injury (TBI). The primary and secondary clinical outcome measures were in-hospital mortality and survival, respectively, and the immediate as well as long-term surgical wound issues.Results There were 40 cases, 38 men (95%) and 2 women over a 40-month period with a mild (n = 8), moderate (n = 17), or severe TBI (n = 15). As assessed by the computed tomography Rotterdam score, life-threatening significant brain injury was present in 90%. Poor clinical outcome occurred in about a third of cases (32.5%) mainly in the severe TBI group (77% of poor outcome) and not in the mild TBI group. Surgical site complications occurred in four patients (10%)Conclusions The presented modified temporal muscle hDC technique offers significant economic advantages over the traditional surgical method of DC without added complications. Analysis of the clinical data in a consecutive prospective cohort of patients with potentially fatal TBI who underwent this surgical procedure showed a good outcome in at least two thirds.
Keywords: decompressive craniectomy; hinge decompressive craniectomy; low-resource practice; surgical technique; outcome study